Seasonal Variation in Chemical Composition of Achyranthes aspera Linn. and A. bidentata Bl. - Ratra, Parmindar S.; Misra, K. C. (Indian Forester, 1970)
The paper deals with chemical composition ot Achyranthes aspera Linn. and A.bidentata BI. collected during summer and winter seasons from Varanasi and Mussoorie respectively. Plant material collected from both the areas has been studied for the alkaloidal and mineral composition especially, N, K, P, Na and Ca, and the results are reported in this communication. There is considerable variation in the mineral accumulation by the two species during the two seasons.